The Rise of Indonesian Feminist Activism on Social Media - Gilang Desti Parahita (Ikatan Sarjana Komunikasi Indonesia, 2019)
Some studies have discussed digital activism and politics in Indonesia. However, studies investigating the phenomenon of Indonesian feminist activism on social media have yet to be conducted. On the other hand, Facebook, YouTube, Instagram, and also other online platforms have become a fertile site for the public to aspire their views and mobilize people for some causes, including social media accounts voicing feminist perspectives in Indonesian online sphere. This study uncovers the actors behind and goals of feminism activists who create accounts on social media such as Facebook, Instagram and YouTube. The method of the study is snow-ball interviews, content analyses of Instagram posts, and close observation on public activities of the important figures within the movement on their social media account, as well as their writings. This study found that Indonesian digital feminism activists have started with the agencies of the young women of Indonesia in the circle of senior feminists in Jakarta, as well as feminist emerging from the GusDurian network. Basic literacy and digital literacy have facilitated the activists with capability to articulate and share their ideas. Eventually, the activists initiate the movement on social media which functions as a means of creating digital safe place, sharing personal stories, providing online discussion forum, promoting marches and offline discussion events, responding to criticisms and oppositional standpoints, as well as conducting and publishing research.